2019
DOI: 10.1186/s10033-019-0388-9
|View full text |Cite
|
Sign up to set email alerts
|

Signal-Based Intelligent Hydraulic Fault Diagnosis Methods: Review and Prospects

Abstract: Hydraulic systems have the characteristics of strong fault concealment, powerful nonlinear time-varying signals, and a complex vibration transmission mechanism; hence, diagnosis of these systems is a challenge. To provide accurate diagnosis results automatically, numerous studies have been carried out. Among them, signal-based methods are commonly used, which employ signal processing techniques based on the state signal used for extracting features, and further input the features into the classifier for fault … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 83 publications
0
35
0
1
Order By: Relevance
“…As a result of rapid technological development, traditio nal systems of automation and standard methods of production (compliance with the technological regulations, reducing intermediate losses through modernization of the production facility, process coordination of the adjacent areas [2]) are not sufficient as the means of receiving high profits. Managers of industrial enterprises are likely to introduce intelligent systems at their production sites [3], which are based on various modern methods and technologies [4][5][6]. The most popular among them are the use of robust [7,8], multidimensional optimal regulators [9], diagnostics [10], neural networks [11], fuzzy logic, scenario-target approach [12,13] and others.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…As a result of rapid technological development, traditio nal systems of automation and standard methods of production (compliance with the technological regulations, reducing intermediate losses through modernization of the production facility, process coordination of the adjacent areas [2]) are not sufficient as the means of receiving high profits. Managers of industrial enterprises are likely to introduce intelligent systems at their production sites [3], which are based on various modern methods and technologies [4][5][6]. The most popular among them are the use of robust [7,8], multidimensional optimal regulators [9], diagnostics [10], neural networks [11], fuzzy logic, scenario-target approach [12,13] and others.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…On account of the intensity of operation and varying working conditions, the frequent machinery faults may result in the unexpected severe losses in safety and economy [1,2]. As a typical interdisciplinary cooperation, fault diagnostic techniques can be categorized into the following three categories, modelbased methods, knowledge-based methods, and signal-based methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a comprehensive review of the basic research on machinery fault diagnosis, Chen et al [3] reviewed the past, summarized the present and analysed future trends, focusing on the four key steps in fault diagnosis: fault mechanism, sensor technique and signal acquisition, signal processing, and intelligent diagnostics. Additional reviews have focused on specific aspects, such as signal processing techniques in fault diagnosis [2,[4][5][6][7][8][9][10][11][12][13][14], fault diagnosis in condition-based maintenance (CBM) and prognostics and health management (PHM) [15], fault diagnosis of bearings, gearboxes and turbines [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and AI techniques in fault diagnosis [32][33][34][35]. These reviews have identified various topical issues covered within the emergent research literature and have provided valuable research insight into the corresponding themes.…”
Section: Introductionmentioning
confidence: 99%